ECONOMIC INTEGRATION OF UKRAINE: CONTEXT OF THE RUSSIAN-UKRAINIAN WAR - SHNYRKOV, Oleksandr; CHUGAIEV, Oleksii (Journal of European Economy, 2023)
Integration with the large market of the EU creates additional competitive advantages for Ukraine. The Association Agreement and the Deep and Comprehensive Free Trade Area (DCFTA), the status of the candidate country and international assistance, which aim to approximate Ukraine’s legislation to EU norms, have become the institutional instruments of such integration. Over the recent years, the European Union has become Ukraine’s main trade and investment partner. The basis of Ukrainian exports to the EU is formed mainly by crops and metallurgical products. The main items of Ukraine’s imports are supplies of machine-building equipment and fuels. In terms of grains and oil crops, Ukraine is the main supplier to the EU. Under the conditions of war, the foreign trade with the EU has proven itself to be robust in volume and, in contrast to other vectors of trade, diversified. This was facilitated by the elimination of a number of tariff and non-tariff restrictions on Ukrainian exports to the EU, as well as the realignment of the logistics infrastructure towards the West. The structure of Ukrainian exports to the EU has seen an increase in the role of a range of agricultural products, along with a sharp decline in the role of metals. On the other hand, the EU has become an important supplier of military products and fuels to Ukraine. Along with that, with the question of security unresolved, the insufficient investment attractiveness remains to be a problematic aspect for Ukraine. JEL: F14, F15, F35, F51.